Zinc, insulin, and the liver: a ménage à trois - O’Halloran, Thomas V. (American Society for Clinical Investigation, 2013)
Insulin and Zn(2+) enjoy a multivalent relationship. Zn(2+) binds insulin in pancreatic β cells to form crystalline aggregates in dense core vesicles (DCVs), which are released in response to physiological signals such as increased blood glucose. This transition metal is an essential cofactor in insulin-degrading enzyme and several key Zn(2+) finger transcription factors that are required for β cell development and insulin gene expression. Studies are increasingly revealing that fluctuations in Zn(2+) concentration can mediate signaling events, including dynamic roles that extend beyond that of a static structural or catalytic cofactor. In this issue of the JCI, Tamaki et al. propose an additional function for Zn(2+) in relation to insulin: regulation of insulin clearance from the bloodstream.